Pertanggungjawaban Pidana Penanam Ganja Berdasarkan Undang-Undang tentang Narkotika - Siagian, Fahrizal S (Kajian Ilmiah Hukum dan Kenegaraan, 2023)
Purpose: Narcotics abuse is a chronic problem that plagues Indonesia. Narcotics are not intended for purposes other than medical purposes. However, there are still people who still dare to plant marijuana trees which are strictly prohibited as regulated in Articles 111 and 112 Paragraph 1 of Law Number 35 of 2009 concerning Narcotics which explains the prohibition on growing marijuana unlawfully. The formulation of the problem in this research is first, How is Narcotics Crime Regulated in Indonesia? Second, what is the criminal responsibility of marijuana growers according to Law Number 35 of 2009 concerning Narcotics? The aim of the research is to answer this research problem. Methodology: The type of research used is normative legal research which refers to research studies on statutory regulations combined with primary, secondary and tertiary legal materials. The data collection technique is by using Library Research. The nature of the research is descriptive analysis. Results: The research results show that Indonesia has strict regulations that do not legalize narcotics carelessly, the prohibition is regulated in Article 111 Paragraphs 1, 2 and 112 Paragraphs 1, 2 of Law 35 of 2009 concerning Narcotics. Second, every person who without right or against the law plants, maintains, owns, stores, controls or provides narcotics in the form of plants legally and convincingly can be held criminally liable. In conclusion, Indonesia as a legal country has strict regulations to protect the young generation of the Indonesian nation from the dangers of narcotics abuse. Every person who owns, processes and distributes narcotics against their rights can be held liable for imprisonment for a minimum of 4 years, a maximum of 12 years, a fine of at least 800 million and a maximum of 8 billion rupiah. Limitation: This research is to explain and/or describe and describe all data obtained from data sources related to criminal liability for marijuana growers. Contribution: Indonesia does not legalize the use of narcotics against the law. If this happens, they can be held criminally liable.